The Influence of E-WOM and Price Through Booking.com on Purchase Interest at Courtyard by Marriott Bali Nusa Dua Resort - Prabhawati, Luh Gde Ayu; Pitanatri, Putu Diah Sastri; Adyatma, Prastha (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this research is to identify the influence of E-WOM and Price via booking.com on purchase intention. This research was conducted at the Courtyard by Marriott Bali Nusa 2 Resort hotel. The population in this research involved 100 respondents who had not had the chance to stay at the Courtyard by Marriott Bali Nusa 2 Resort hotel. The type of information used in this research is quantitative information. This research uses primary information in the form of a questionnaire distributed to respondents. The illustration collection method used is non-probability sampling (purposive sampling). The analysis method uses multiple linear regression with SPSS version 29 for Windows. The results of this research prove that E-WOM (X1) partially has a positive and significant effect on Purchase Intention with a calculated ttable value = 4, 1271, 660 and a significance value of & ???? = 0.001 & 0.05. Price (X2) partially has a positive and significant effect on purchase intention with a calculated ttable value of 6.256>1.660 and a significance value of & ????= 0.001 & 0.05. E-WOM and Price simultaneously have a positive and significant effect on Purchase Intention with a calculated Ftable value of 26.721 <3.94 and a significance value of & ∝= 0.001 & 0.05. Thus, it can be concluded that the results of this research prove that E-WOM and Price have a positive and significant effect on purchase intention, and simultaneously have an effect on purchase intention.